Evolution of magnetic phases located in Boyacá clays subject to high temperatures - Ruge-Guerrero, Oscar Orlando; Martínez-Ovalle, Segundo Agustín; Díaz-Lagos, Mercedes (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
In this paper we analyze clay samples obtained from the region of Tunja Boyacá to study the effect of heating temperature in the color of these materials and at the same time as indicative of the nature and distribution of constituents iron oxide Fe2 O3 . These colors are of decorative importance in the manufacture of roofing and brick housing construction. X-ray Fluorescence (XRF), X-ray Diffraction (XRD), Mössbauer Spectroscopy (MS) and Scanning Electron Microscopy (SEM) for samples subjected to heat treatment between (400-1200 ⁰C) was used to assess the evolution of the phases and microstructure in the samples. The results indicate that the spectral properties of the samples are influenced primarily by the mineralogy of Fe. Goethite and hematite phases were identified in all samples. Mössbauer analyzes indicated that with increasing temperature of the raw clay presents an increase in phase of hematite and the red tone from the body of the same, in contrast to samples of yellow tone natural clay . Hematite formation and increased its magnetic ordering is largely due to the disappearance of organic matter and the oxidation of iron ions arranged in mineralogical phases of raw clay.